Probabilistic cost-effectiveness analysis of cascade screening for familial hypercholesterolaemia using alternative diagnostic and identification strategies. Issue 14 (17th June 2011) - Nherera, L; Marks, D; Minhas, R; Thorogood, M; Humphries, S E
Abstract : Objective: To estimate the probabilistic cost-effectiveness of cascade screening methods in familial hypercholesterolaemia (FH) from the UK NHS perspective. Design: Economic evaluation (cost utility analysis) comparing four cascade screening strategies for FH: Using low-density lipoprotein (LDL) cholesterol measurements to diagnose affected relatives (cholesterol method); cascading only in patients with a causative mutation identified and using DNA tests to diagnose relatives (DNA method); DNA testing combined with LDL-cholesterol testing in families with no mutation identified, only in patients with clinically defined 'definite' FH (DNA+DFH method); DNA testing combined with LDL-cholesterol testing in no-mutation families of both 'definite' and 'probable' FH patients (DNA+DFH+PFH). A probabilistic model was constructed to estimate the treatment benefit from statins, with all diagnosed individuals receiving high-intensity statin treatment. Population: A cohort of 1000 people suspected of having FH aged 50 years for index cases and 30 years for relatives, followed for a lifetime. Main outcomes: Costs, quality-adjusted life-years (QALY) and incremental cost-effectiveness ratios (ICER). Results: The DNA+DFH+PFH method was the most cost-effective cascade screening strategy. The ICER was estimated at £3666/QALY. Using this strategy, of the tested relatives 30.6% will be true positives, 6.3% false positives, 61.9% true negatives and 1.1% false negatives. Probabilistic sensitivity analysis showed that this approach is 100% cost-effective using the conventional benchmark for cost-effective treatments in the NHS of between £20 000 and £30 000 per QALY gained. Conclusion: Cascade testing of relatives of patients with DFH and PFH is cost-effective when using a combination of DNA testing for known family mutations and LDL-cholesterol levels in the remaining families. The approach is more cost-effective than current primary prevention screening strategies.